A case report of ectopic fibroid: Vaginal leiomyoma - Che Hasnura CH; Yulianty A; Zainul Rashid MR; Nirmala K (Department of Surgery, UKM Medical Centre, 2011)
We hereby report a rare case of a woman who presented with symptoms of urogenital prolapse and menorrhagia. She was erroneously diagnosed to have cervical mass and underwent examination under anesthesia and was found to have only a vaginal leiomyoma. The fibroid was enucleated successfully through a vaginal incision. We discuss the rare case